Karakterisasi Molekuler dan Studi Filogenetik Virus African Swine Fever pada Kejadian Wabah di Sumatera Utara Tahun 2019 - 2023 - Panggabean, Ruben Hasiholan; Mayasari, Ni Luh Putu Ika; Faisal, Faisal; Wibawan, I Wayan Teguh (Jurnal Sain Veteriner, 2024)
African swine fever is a viral disease that causes hemorrhagic fever in domestic pigs and wild swine worldwide. The first case of ASF in Indonesia was reported in North Sumatra Province in September 2019. A total of 20 archival samples of positive ASF collected from the Animal Disease Investigation Center of Medan during the outbreak investigation took place from 2019 to 2023, were used in this study. The partial B646L gene (p72), the full sequence of the E183L gene (p54) and the central variable region (CVR) of the B602L gene were amplified, purified, then sequenced. Web-based BLAST program and MEGA XI software were used to analyze the nucleotide sequencing results. The results of molecular and phylogenetic characterization analysis revealed that the ASF virus that infected pigs in North Sumatra Province in 2019-2023 was belonged to genotype II. Analysis of the three genes (B646L, E183L and B602L) did not show changes in the nucleotide and amino acid sequences in the isolates in the last 5 years. No novel variants were found in the CVR gene B602L. CVR analysis showed that these ASF virus strain belonged to subgroup XXXII. The results of this study revealed that the ASF virus in North Sumatra Province has high homology with ASF virus isolates previously detected in China, Vietnam and East Leste in 2019.